(3GdSdhc GdJfXjej (B:s (3fXQjGJ hfeGPL hJWHjb Yedj dEOGQI GdSdhc aj GdefXeI (B/s - (3EOQjS, KGHJ YHO GdQMefs; (3eMeO GdeQSi, LeGd GdOjf s ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2002)
(3GdSdhc GdJfXjej(B((3eaGgje(B)-(3HMhK GdSdhc GdJfXjej(B((3GdJYde ,GdEOQGc,GdEJLGgGJ,bjGS GdEJLGgGJ,GdOGaYjI,GdeMOOGJ GdELJeGYjI(B)_(3GdSdhc GdJfXjej aj GdJWHjb GdEOGQj(B-(3OjfGejcjI GdLeGYI aj GdefXeGJ(B-(3Sdhc GdeLehYGJ hGdUQGY GdJfXjej(B-(3GdVZhW GdJfXjejI(B-(3GdbjGOI hGdJCKjQ aj GdBNQjf(B-(3EOGQI GdYdGbGJ GdTNUjI hGdEJUGdGJ(B-(3EJNGP GdbQGQGJ GdLeGYjIs
Keywords: (3GdSdhcs; (3JfXje hEOGQIs; (3Yde GdfaS GdELJeGYjs